Growth Mindset Predicts Cognitive Gains in an Older Adult Multi-Skill Learning Intervention. (June 2023) - Sheffler, Pamela; Kürüm, Esra; Sheen, Angelica M.; Ditta, Annie S.; Ferguson, Leah; Bravo, Diamond; Rebok, George W.; Strickland-Hughes, Carla M.; Wu, Rachel
Growth mindset (belief in the malleability of intelligence) is a unique predictor of young learners' increased motivation and learning, and may have broader implications for cognitive functioning. Its role in learning in older adulthood is unclear. As part of a larger longitudinal study, we examined growth mindset and cognitive functioning in older adults engaged in a 3-month multi-skill learning intervention that included growth mindset discussions. Before, during, and after the intervention, participants reported on their growth mindset beliefs and completed a cognitive battery. Study 1 indicated that intervention participants, but not control participants, increased their growth mindset during the intervention. Study 2 replicated these results and found that older adults with higher preexisting growth mindsets showed larger cognitive gains at posttest compared to those with lower preexisting growth mindsets. Our findings highlight the potential role of growth mindset in supporting positive learning cycles for cognitive gains in older adulthood.